2014
DOI: 10.1007/s10584-014-1223-z
|View full text |Cite
|
Sign up to set email alerts
|

Operationalizing climate targets under learning: An application of cost-risk analysis

Abstract: Cost-Effectiveness Analysis (CEA) determines climate policies that reach a given climate target at minimum welfare losses. However, when applied to temperature targets under climate sensitivity uncertainty, decision-makers might be confronted with normatively unappealing negative expected values of future climate information or even infeasible solutions. To tackle these issues, Cost-Risk Analysis (CRA), that trades-off the costs for mitigating climate change against the risk of exceeding climate targets, has b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3
1

Relationship

2
6

Authors

Journals

citations
Cited by 33 publications
(51 citation statements)
references
References 36 publications
1
47
0
3
Order By: Relevance
“…From a political point of view, therefore, an alternative called Cost-Risk Analysis (CRA) was suggested that circumvents the inconsistencies of CEA (Schmidt et al, 2011 andNeubersch et al, 2014). Instead of including climate damage functions, CRA weighs the risks of transgressing a predefined temperature target against the costs of mitigation, representing a hybrid of 20 CBA and CEA.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…From a political point of view, therefore, an alternative called Cost-Risk Analysis (CRA) was suggested that circumvents the inconsistencies of CEA (Schmidt et al, 2011 andNeubersch et al, 2014). Instead of including climate damage functions, CRA weighs the risks of transgressing a predefined temperature target against the costs of mitigation, representing a hybrid of 20 CBA and CEA.…”
Section: Introductionmentioning
confidence: 99%
“…Instead of including climate damage functions, CRA weighs the risks of transgressing a predefined temperature target against the costs of mitigation, representing a hybrid of 20 CBA and CEA. Thereby, an evaluation of the 2°C target remains possible, even in cases that would be infeasible under CEA (Neubersch et al, 2014). The value system of the 2°C target can be extrapolated into any future scenario.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, we may conclude that the overall uncertainty about forest management under climate change may be reduced in the future depending on international cooperation and commitments along with technological advancements. This conclusion highlights the value of learning and obtaining novel knowledge about climate change [32] by monitoring forest responses to a combined effect of climate and management, and the necessity to consider robust decisions and avoid high economic loss (see an example in the BDealing with Deep Uncertainty of Climate Change^section). It is worth highlighting that the difficulty in modeling extreme climate events and the imposed high impacts on forests health and productivity remains a challenging issue as there is no historical parallel to build the climate model predictions upon [33].…”
Section: Change In Framework By Consensus About Target Global Warmingmentioning
confidence: 96%
“…The properties and consequences of this new decision analytic tool are at present subject to academic investigation( 8 ). Neubersch et al [30] utilize a version of CRA that linearly penalizes a transgression of a temperature target. They argue it was the most conservative way to formulate a risk function that would still avoid any counterintuitive "tipping" towards a high-emission path, once a target has been missed.…”
Section: Lnes 2014mentioning
confidence: 99%
“…could be up to hundreds of billions of Euro per year [30] which could be seen as an incentive to invest faster in improved climate observation and modelling systems. Finally, does the above development of a new decision-analytic tool like CRA imply in part a "rehabilitation" of CBA from the perspective of the "CEA community"?…”
Section: Lnes 2014mentioning
confidence: 99%